Bioinformatics and functional analysis of glutathione s-transferases of Pseudomonas putida KT2440 / Nasiru Abdullahi - Nasiru , Abdullahi (2018)
Heavy metals and toxic aromatic hydrocarbons are released into the environment by different ways. The resultant effect causes health threat to human and the ecosystem. Several strategies could be adopted towards mopping these toxic pollutants. Among the strategy adopted in mopping out these toxicants is the use of microorganisms. In this thesis, glutathione S-transferases (GSTs) were studied in a bacteria strain (Pseudomonas putida KT2440) well known for its detoxification ability. GSTs are enzymes mostly involved in detoxification ability of many organisms, although less information is known on bacteria GSTs. Bioinformatic analysis were performed and results revealed 13 putative GSTs which were not characterized prior to this PhD research. Phylogenetic results showed that most of the GSTs in P. putida KT2400 are widely expanded within the known classes of bacterial GSTs, with predominant GSTs falling under the beta and chi class. Transcriptional factors involved in detoxification ability of some studied GSTs were identified in either/both 5΄and 3΄region of six putative GST genes. Predicted protein- interaction partners have shown a possible diverged function of the GSTs. Six putative GSTs showed strong interaction with glutathione reductase, peroxidase and gamma-glutamyltransferase. This is an indication of involvement in oxidative stress. In order to understand some GST roles of this strain; one of the GSTs (GST8; PP_2474) was further studied. The gene was cloned, purified and overexpressed. The encoded protein consists of 206 amino acids with molecular weight of 23.7kDA. Recombinant protein was purified by Ni-affinity chromatography. The purified protein gave activity with environmental pollutants; dichloromethane and dinitrotoluene (DNT). Molecular Docking analysis revalidates the binding affinity with these pollutants. Moreover, it has exhibits a peroxidase activity, an indication that it may participates in oxidative stress of P. putida KT2440. Base on the afore-mentioned activities, homology modelling, sequence and phylogenetic analyses GST8 was proposed to be a new theta-like bacteria GST. It might be a candidate gene for detoxification of trinitrotoluene (TNT) contaminated areas. Furthermore, another putative GST (GST10; PP_2933) was studied. The encoded protein consists of 280 amino acids with molecular weight of 30 kDa. The purified protein of GST10 gave activity with trans-2-octenal and cumene peroxide. The transformed recombinant plasmid of GST10 shows a high resistance to Fe metal concentrations at 2 mM. This is an indication that the protein has an iron-binding site and might do so to stabilize the structure or to give more access to the substrates at the active site. Resistance to Fe toxicity of the transformed cells is probably due to GST10 recombinant clone. Isothermal Calorimetry analyses confirms a positive interaction between the protein and iron metal. The recombinant clone of GST10 might be good in bioremediation of iron toxicity. GST10 is proposed to be a new (Nu–like) bacteria GST as it shares 69% sequence identity with an unusual Nu-class GST from E. coli (YghU). Besides, peroxidase activity is the main feature of both GST10 and YghU. Keywords: glutathione s-transferase, Pseudomonas putida KT2440, bioremediation, dinitrotoluene, dichloromethane